(untitled) (Revista de Estudos da Linguagem, 2006)
In this paper I analyze the phenomenon by which an auxiliary verb selectsthe form of its complement, a morphossyntactic dependency. For myanalysis I will adopt the claim of Minimalist Program that derivation ofsyntactic structures is result of manipulations of features of lexicalitems. With this idea I will argue that morphossyntactic dependencyimposed by auxiliary verbs to their complements is a reflex ofinteraction of features of auxiliary verbs and features of theircomplements. To implement my analysis, I will propose that: (a) nonfiniteforms of verbs (infinitive, gerund and past participle), which occurin complement position of auxiliaries, are specified for features ofMood and Aspect and (b) auxiliary verbs select features of Aspect andMood from their complements.